Performing registers and registering performance: Young children's linguistic practices during play in the Greek Cypriot context. (September 2017) - Ioannidou, Elena
Abstract: The current paper explores language use among a group of preschool Greek Cypriot children during their play time at home. Based on theories of performance and register-formation the paper draws on ethnographic data in order to investigate the way Standard Modern Greek and the Cypriot Greek are used in children's micro-interactions. The methodology adopted was case study research of a network of five children for a period of eighteen months and the main data collection techniques were participant and non-participant observation of the children during their play activities, with audio recordings and rich field notes. Data analysis indicated that the two varieties were used in a dynamic way by the children to form collaborations during play time, to enact social roles, to reflect cultural values and ultimately to contribute through their performances in register (re)formation. Highlights: Preschool children using multiple linguistic varieties as performative tools. Language as enactment for forming collaborations and claiming spaces during play. Children's linguistic interactions reflected cultural and political norms. New type of performances emerged leading to reorganization of registers in the Greek Cypriot context.